The development of cervical intraepithelial neoplasia in three members of the same family: a case report - Vinokurov, M. A.; Minaeva, A. V.; Leshkina, G. V.; Romanyuk, T. N.; Mironov, K. O.; Akimkin, V. G. (Frontiers in Reproductive Health, 2025)
BackgroundCervical cancer is the fourth most common cancer and cause of cancer-related death among women globally. Familial cases of cervical cancer highlight the potential role of genetic factors in its development. This study aims to present a clinical case of cervical intraepithelial neoplasia (CIN) affecting a woman and her two daughters.Case descriptionThis report describes a familial case involving three patients diagnosed with cervical lesions: (1) Patient A: A 27-year-old woman presented with complaints of postcoital bleeding. She was diagnosed with high-grade squamous intraepithelial lesion (HSIL, CIN3). Radiowave conization of the cervix was performed, and histological examination confirmed the diagnosis of CIN3. (2) Patient B: A 25-year-old woman, the sister of Patient A, also presented with contact bleeding. She was similarly diagnosed with HSIL (CIN3). A radiowave conization procedure was performed successfully, with histopathological analysis confirming the diagnosis. (3) Patient C: A 52-year-old woman, the mother of Patients A and B, was diagnosed with low-grade squamous intraepithelial lesion (LSIL, CIN1) following cytological examination. She declined further diagnostic and therapeutic interventions. Genetic testing for all three patients revealed the presence of risk alleles associated with cervical cancer predisposition (rs10175462, rs1048943, rs4646903) and the absence of protective genotypes.DiscussionFamilial cases of CIN are rare and suggest a potential genetic predisposition to the disease. The identification of common genetic polymorphisms underscores the role of hereditary factors in cervical cancer pathogenesis. These findings emphasize the importance of incorporating family history and genetic assessments into screening, diagnosis, and treatment strategies.ConclusionThis case highlights the significant influence of genetic factors in the development of cervical intraepithelial neoplasia. It underscores the need for further research to enhance strategies for early detection, prevention, and management of cervical cancer in individuals with elevated genetic risk.